Rapid electrophoretic deposition of biocompatible graphene coatings for high-performance recording neural electrodes. Issue 42 (19th October 2022) - Dong, Miheng; Coleman, Harold A.; Tonta, Mary A.; Xiong, Zhiyuan; Li, Dan; Thomas, Sebastian; Liu, Minsu; Fallon, James B.; Parkington, Helena C.; Forsythe, John S.
Abstract : A thin graphene oxide(GO) coating was electrophoretically deposited on Pt/Ir neural electrodes. Followed by electrochemical reduction, the rGO coated electrodes exhibited excellent biocompatibility and improved in vivo neural recordings. Abstract : The electrical and biological interfacial properties of invasive electrodes have a significant impact on the performance and longevity of neural recordings in the brain. In this study, we demonstrated rapid electrophoretic deposition and electrochemical reduction of graphene oxide (GO) on metal-based neural electrodes. Scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and other characterizations confirmed the existence of a uniform and effectively reduced graphene oxide coating. Electrochemically reduced graphene oxide (ErGO) coated Pt/Ir neural electrodes exhibited 15.2-fold increase in charge storage capacity (CSC) and 90% decrease in impedance with only 3.8% increase in electrode diameter. Patch clamp electrophysiology and calcium imaging of primary rat hippocampus neurons cultured on ErGO demonstrated that there was no adverse impact on the functional development of neurons. Immunostaining showed a balanced growth of excitatory and inhibitory neurons, and astrocytes. Acute recordings from the auditory cortex and chronic recordings (19 days) from the somatosensory cortex found ErGO coating improved the performance of neural electrodes in signal-to-noise ratio (SNR) and amplitude of signals. The proposed approach not only provides an in-depth evaluation of the effect of ErGO coating on neural electrodes but also widens the coating methods of commercial neural electrodes.